2012
DOI: 10.1007/s00592-012-0418-x
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 gene polymorphisms and type 2 diabetes: association with diabetic retinopathy and cardiovascular autonomic neuropathy

Abstract: Type 2 diabetes (T2DM) is a complex disease resulting from the contribution of both environmental and genetic factors. Recently, the list of genes implicated in the susceptibility to T2DM has substantially grown, also as a consequence of the great development of the genome-wide association studies in the last decade. Common polymorphisms in TCF7L2 gene have shown to have a strong effect with respect to many other involved genes. The aims of our study were to confirm the role of TCF7L2 in the susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 32 publications
2
59
1
4
Order By: Relevance
“…Buraczynska et al [12] reported association of rs 7903146 with nephropathy, diabetic retinopathy and Cardiomyopathy, while Ciccacci et al [13] Egger's test for intercept showed no evidence of publication bias (intercept = -0.76, SE = 1.50, 95% CI = -4.44 to 2.90, p 2 tailed = 0.62). Classic Fail safe 'N' = 223, missing from the analysis for every published study included, which further supports absence of publication bias.…”
Section: Resultsmentioning
confidence: 99%
“…Buraczynska et al [12] reported association of rs 7903146 with nephropathy, diabetic retinopathy and Cardiomyopathy, while Ciccacci et al [13] Egger's test for intercept showed no evidence of publication bias (intercept = -0.76, SE = 1.50, 95% CI = -4.44 to 2.90, p 2 tailed = 0.62). Classic Fail safe 'N' = 223, missing from the analysis for every published study included, which further supports absence of publication bias.…”
Section: Resultsmentioning
confidence: 99%
“…Among the most common diabetic complications, some susceptible genes have been proposed to be independent factors, despite the duration of diabetes and HbA1c level. For instances, in a cohort, case-control and genotype-phenotype correlation study involving over 320 patients, TCF7L2 gene was significantly associated with diabetic retinopathy and autonomic neuropathy of cardiovascular diseases (Ciccacci et al, 2013). In addition, genetic linkage and characteristic analyses resulted that genes responsible for lipoprotein metabolism, PPARs (Peroxisome proliferator-activated receptors), cytokines, chemokines, and KLFs (Krüppel-like family of transcription factors) associated type 2 DM and coronary heart disease (Akbar, 2015).…”
Section: The Limitations Of Respective Theoriesmentioning
confidence: 99%
“…This study had a reasonable sample size (n = 1,139 in the discovery and replication cohorts combined), used the PDR phenotype, and defined controls stringently with a minimum diabetes duration of 15 years. TCF7L2 had already been studied in DR with both positive [33,34] and negative results [32,35]. Further investigation in other T2D populations is warranted.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%
“…The T allele frequency in the diabetic peripheral neuropathy group was lower than in T2D control (p = 0.001). In 154 Italian patients with T2D and 171 healthy controls, an association between the TCF7L2 rs7903146 variant and the presence of cardiovascular autonomic neuropathy has been reported (p = 0.02) [34]. Samples from subjects with diabetic neuropathy have also been evaluated for mutations in the AKR1B1 gene (exon 1) [97].…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%